Agtechs: uma análise do ambiente de negócio paranaense - Blanco, Thiago Henrique Martinez (2019)
This work analyzed the structure of the business environment and the articulation between the actors in the Agtechs paranaense ecosystem. The methodology used was a qualitative, exploratory and descriptive approach. The data collection procedure was done through the application of semi-structured interviews resulting in 19 case studies, the criterion for choosing the participants was the distribution and performance in the mesoregions of the State and, to analyze the data of the research, the technique of content analysis. It is concluded in this research that Paraná occupies the third place with 25 Agtechs, 12% in the national panorama. The North Central and Southwest regions, concentrate 63% of the State. It can be affirmed that the Paraná ecosystem is in a learning and maturing phase, where resistance and institutionalism between the actors is evident, causing slowness and lack of focus on practical results. The main resources are training or consulting, specialists researchers, but lack mentoring with experience in the agro to meet in a personalized way the needs of Agtechs. It is suggested as a future study some developments, such as: (i) to measure the relations of articulation and the results generated in the promotion of new business for all the actors of the ecosystem; (ii) to evaluate Agtechs' articulation model in other locations in Brazil and to compare it with the results of the Paraná ecosystem; (iii) investigate the business environment of more developed ecosystems like Israel and the United States to find the competitive differentials of these countries; and (iv) analyze the financial feasibility of investment for the development of regional innovation centers focused on the development of applied research and business creation.